2003
DOI: 10.1128/aem.69.4.2321-2329.2003
|View full text |Cite
|
Sign up to set email alerts
|

Rope-Producing Strains of Bacillus spp. from Wheat Bread and Strategy for Their Control by Lactic Acid Bacteria

Abstract: Two types of white wheat bread (high-and low-type loaves) were investigated for rope spoilage. Thirty of the 56 breads tested developed rope spoilage within 5 days; the high-type loaves were affected by rope spoilage more than the low-type loaves. Sixty-one Bacillus strains were isolated from ropy breads and were characterized on the basis of their phenotypic and genotypic traits. All of the isolates were identified as Bacillus subtilis by biochemical tests, but molecular assays (randomly amplified polymorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(80 citation statements)
references
References 33 publications
2
74
0
4
Order By: Relevance
“…Bacillus species are frequently found in food (9,14,46), which could facilitate their entry into the different gut ecosystems. Earlier studies have reported on the frequent isolation of B. cereus from human feces (11,65), and a recent study has reported the identification of B. subtilis, B. licheniformis, B. pumilus, and Bacillus fragilis in the cecum of rabbits and the role of sporulation by B. subtilis in the induction of gut-associated lymphoid tissue development (55).…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus species are frequently found in food (9,14,46), which could facilitate their entry into the different gut ecosystems. Earlier studies have reported on the frequent isolation of B. cereus from human feces (11,65), and a recent study has reported the identification of B. subtilis, B. licheniformis, B. pumilus, and Bacillus fragilis in the cecum of rabbits and the role of sporulation by B. subtilis in the induction of gut-associated lymphoid tissue development (55).…”
Section: Discussionmentioning
confidence: 99%
“…plantarum in sourdough production is not only important for the generation of acids, but also for several other positive effects expressed during fermentation. L. plantarum has been reported as inhibitor of rope-producing B. subtilis (Pepe et al, 2003;Menteş et al, 2007). It is able to produce bacteriocins, namely plantaricin (Todorov et al, 1999), and antifungal compounds (Lavermicocca et al, 2000;Magnusson et al, 2003;Ryan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The study extends current knowledge on the effect of exopolysaccharide production by cereal-associated lactic acid bacteria. (3,9,10,42,44,45). The LAB strains, complete with origins and references, are presented in Table S1 in the supplemental material.…”
mentioning
confidence: 99%